Ultraviolet damage and repair maps in Drosophila reveal the impact of domain-specific changes in nucleosome repeat length on repair efficiency - Morledge-Hampton, Benjamin; Selvam, Kathiresan; Chauhan, Manish; Goodman, Alan G.; Wyrick, John J. (Genome Research, 2025)
Cyclobutane pyrimidine dimers (CPDs) are formed in DNA following exposure to ultraviolet (UV) light and are mutagenic unless repaired by nucleotide excision repair (NER). It is known that CPD repair rates vary in different genome regions owing to transcription-coupled NER and differences in chromatin accessibility; however, the impact of regional chromatin organization on CPD formation remains unclear. Furthermore, nucleosomes are known to modulate UV damage and repair activity, but how these damage and repair patterns are affected by the overarching chromatin domains in which these nucleosomes are located is not understood. Here, we generated a new CPD damage map in Drosophila S2 cells using CPD-seq and analyzed it alongside existing excision repair-sequencing (XR-seq) data to compare CPD damage formation and repair rates across five previously established chromatin types in Drosophila. This analysis revealed that repair activity varies substantially across different chromatin types, whereas CPD formation is relatively unaffected. Moreover, we observe distinct patterns of repair activity in nucleosomes located in different chromatin types, which we show is owing to domain-specific differences in nucleosome repeat length (NRL). These findings indicate that NRL is altered in different chromatin types in Drosophila and that changes in NRL modulate the repair of UV lesions.